2012
DOI: 10.1186/1758-2555-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dimorphic landing mechanics and their role within the noncontact ACL injury mechanism: evidence, limitations and directions

Abstract: Anterior cruciate ligament (ACL) injuries continue to present in epidemic-like proportions, carrying significant short- and longer-term debilitative effects. With females suffering these injuries at a higher rate than males, an abundance of research focuses on delineating the sex-specific nature of the underlying injury mechanism. Examinations of sex-dimorphic lower-limb landing mechanics are common since such factors are readily screenable and modifiable. The purpose of this paper was to critically review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 91 publications
(154 reference statements)
0
17
0
Order By: Relevance
“…An ACL injury typically occurs during the landing portion of a jump in ordinary sports activities and has a greater incidence in women than in men 1,2) . ACL deficiency may lead to degenerative changes such as tears of the meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…An ACL injury typically occurs during the landing portion of a jump in ordinary sports activities and has a greater incidence in women than in men 1,2) . ACL deficiency may lead to degenerative changes such as tears of the meniscus.…”
Section: Introductionmentioning
confidence: 99%
“…This supports the use of the LESS as a helpful clinical screening tool because it is able to identify similar sex differences that have been reported in laboratory-based investigations using 3-dimension kinematic instrumentation. 28 To our knowledge, our study is the only investigation to report sex differences in LESS item scores for individuals in the traditional college athletic setting. Previously, Beutler et al 20 compared sex differences across LESS item scores in incoming military cadets and reported that females generally demonstrated poorer jump-landing patterns than their male counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…The investigators reported that there were discrepancies and a lack of consensus between studies for sagittal (eg, knee flexion, hip flexion) and transverse (eg, knee rotation, hip rotation) plane sex differences, but good agreement between studies reporting frontal plane sex differences, particularly for peak knee valgus angle. 28 Furthermore, when considering studies that used similar jump-landing task parameters as the LESS (ie, 30-cm jump-landing height, double-legged landing), the majority of studies reported that females displayed more knee valgus angle at initial ground contact 29,30 and at peak knee valgus angle 29-33 when compared with their male counterparts. The present study reported similar findings as females demonstrated a knee valgus angle at initial ground contact and at maximum knee flexion more than their male counterparts.…”
Section: Discussionmentioning
confidence: 98%
“…Clearly, for the purposes of this paper, we are interested in establishing if there are sex 363 differences in quadriceps activation that are independent of movement strategy, and that 364 might be inferred to be a result of the potential sex differences in PFJ geometry (27). Of 365 course, this is challenging, but there is some preliminary evidence of note.…”
Section: Do Women Exhibit Greater Quadriceps Forces During Movement? 347mentioning
confidence: 99%